Case report and literature review on contrast-induced encephalopathy. (July 2017) - Hamra, Mardi; Bakhit, Yasir; Khan, Mahboob; Moore, Roger
Contrast-induced encephalopathy (CIE) is a rare neurological complication following the administration of injectable intravascular contrast media. Patients with CIE present a wide spectrum of symptoms such as headache, transient cortical blindness, seizure and focal neurological deficits. The diagnosis of CIE requires a high index of suspicion. Its early recognition is of paramount importance in instituting the appropriate supportive treatment in the form of intravenous fluids and also in avoiding unnecessary potentially harmful treatment such as intravenous thrombolysis for suspected ischemic stroke. Here, we report the case of a 62-year-old male patient with a typical presentation of CIE immediately following coronary angiography. We then continue to briefly review the relevant literature on CIE to date.